Welcome to Implementation Science Communications - Rebecca Armstrong (Implementation Science Communications, 2020)
Abstract Implementation research in health is a rapidly growing field. Fourteen years after the launch of Implementation Science, submissions to the journal have grown exponentially, and the journal now uses a high bar for assessing submitted manuscripts. The field of implementation research in health, however, is growing largely through entry of junior researchers with keen interest in the field whose funding histories and research experience are still developing. We consider it essential to support newer entrants to the field and boundary-spanning work that may consist of smaller, pilot studies, as well as those that contribute primarily descriptive findings. As a companion journal to Implementation Science, Implementation Science Communications will accept a broad and diverse range of article types, and provide an important platform for smaller scale or more descriptive research. As with Implementation Science, no specific discipline, research design, or paradigm will be favoured.